Camino winds (Camino Island novels, 2, 1, 2020)
#1 NEW YORK TIMES AND USA TODAY BESTSELLER * "The perfect crime scene ... in the type of wild but smart caper that Grisham's readers love."--Delia Owens, author of Where the Crawdads Sing The master of the legal thriller sweeps you away to paradise for a little sun, sand, mystery, and mayhem. With Camino Winds , America's favorite storyteller offers the perfect escape. Welcome back to Camino Island, where anything can happen--even a murder in the midst of a hurricane, which might prove to be the perfect crime... Just as Bruce Cable's Bay Books is preparing for the return of bestselling author Mercer Mann, Hurricane Leo veers from its predicted course and heads straight for the island. Florida's governor orders a mandatory evacuation, and most residents board up their houses and flee to the mainland, but Bruce decides to stay and ride out the storm. The hurricane is devastating: homes and condos are leveled, hotels and storefronts ruined, streets flooded, and a dozen people lose their lives. One of the apparent victims is Nelson Kerr, a friend of Bruce's and an author of thrillers. But the nature of Nelson's injuries suggests that the storm wasn't the cause of his death: He has suffered several suspicious blows to the head. Who would want Nelson dead? The local police are overwhelmed in the aftermath of the storm and ill equipped to handle the case. Bruce begins to wonder if the shady characters in Nelson's novels might be more real than fictional. And somewhere on Nelson's computer is the manuscript of his new novel. Could the key to the case be right there--in black and white? As Bruce starts to investigate, what he discovers between the lines is more shocking than any of Nelson's plot twists--and far more dangerous. Camino Winds is an irresistible romp and a perfectly thrilling beach read--# 1 bestselling author John Grisham at his beguiling best. Don't miss John Grisham's new book, THE EXCHANGE: AFTER THE FIRM!

Finlay Donovan jumps the gun (Finlay Donovan novels, 3, 1, 2023)
AN INSTANT NEW YORK TIMES BESTSELLER! From USA Today bestseller and Edgar Award nominee Elle Cosimano, comes Finlay Donovan Jumps the Gun --the hilarious and heart-pounding next installment in the beloved Finlay Donovan series. "Fresh, heartfelt and witty, Finlay Donovan Jumps the Gun is a twisty page-turner, and its relatable heroine Finlay Donovan is irresistible!" --Janet Evanovich, #1 New York Times bestselling author of the Stephanie Plum series Dating. Diapers. And dodging bullets. Who said single moms can't have fun? Finlay Donovan has been in messes before--after all, she's an author and single mom who's a pro at getting out bloodstains for rather unexpected reasons--but none quite like this. She and her nanny/partner-in-crime Vero accidentally destroyed a luxury car that they "borrowed" in the process of saving Finlay's ex-husband. The Russian mob handled her debt, but that means Finlay now owes them. Still running the show from behind bars, mob boss Feliks has a task for Finlay: find a contract killer before the cops do. Problem is, the killer might be an officer. Luckily, hot cop Nick has started up a citizen's police academy, so Finlay has the perfect cover-up to sleuth out the real criminal as she does some "research" for her new novel. Nick is more than happy to get close to Finlay, but he's also getting dangerously close to the truth. As Finlay and Vero dodge potential spies and juggle the daily trials of parenting, they can only hope they find the crooked cop before Feliks catches up with them--not to mention revealing Vero's mysterious past, Nick's growing interest in Finlay, and the threat of her looming book deadline.